2004
DOI: 10.1023/b:ifla.0000033022.66289.04
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Effect of Wood Smoke on the Expression of Two Mucin Genes in Rat Airways

Abstract: A short-term, time-dependent smoke exposure of rats in a nose-only chamber to burning wood and 24-h recovery time revealed inflammation of the airways with varying degrees of injury from loss of cilia, degeneration of epithelium, and squamous metaplasia to submucosal edema. These histological changes were reflected in variable expression of the secretory Muc5AC and low expression of membrane-associated Muc4 mucin genes. 20-min smoke exposure in extended recovery experiments showed marked disorder of tracheal e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…An aberrant expression of MUC4 is also detected in human pancreatic tissues from cystic fibrosis patients as compared with the normal pancreas (81). In a recent study (82), transient up-regulation of Muc4 was observed in woodsmoke-treated rats during the recovery phase, suggesting yet another role of MUC4 in the renewal of tracheal epithelium. MUC4 is also aberrantly expressed in epithelial ovarian carcinomas, while exhibiting negligible expression in the normal ovary (83).…”
Section: Muc4 Expression In Malignancies and Inflammatory Diseasesmentioning
confidence: 93%
See 1 more Smart Citation
“…An aberrant expression of MUC4 is also detected in human pancreatic tissues from cystic fibrosis patients as compared with the normal pancreas (81). In a recent study (82), transient up-regulation of Muc4 was observed in woodsmoke-treated rats during the recovery phase, suggesting yet another role of MUC4 in the renewal of tracheal epithelium. MUC4 is also aberrantly expressed in epithelial ovarian carcinomas, while exhibiting negligible expression in the normal ovary (83).…”
Section: Muc4 Expression In Malignancies and Inflammatory Diseasesmentioning
confidence: 93%
“…In general, all mucins play a role in the lubrication of epithelial surfaces and their protection from infections and injuries. Several lines of evidence implicate MUC4 in other important and more sophisticated biological processes as well, such as epithelial cell renewal and differentiation, cell signaling, cell adhesion, and cancer development (26,82,(85)(86)(87)(88).…”
Section: Multifaceted Functions Of the Muc4 Mucinmentioning
confidence: 99%
“…Wood smoke has adverse effects on surfactant48 and cilial function 49. To offset particle oxidative effects, epithelial lining fluid contains high levels of the antioxidant glutathione,50 which is up-regulated after exposure to wood smoke 51.…”
Section: Respiratory Infectionsmentioning
confidence: 99%
“…Some of the pulmonary outcomes that a lot of these studies were aimed at included airway reactivity (Barrett et al 2006;Bhattacharyya et al 2004;Hsu and Kou 2001), asthma exacerbation (Samuelsen et al 2008;Tesfaigzi et al 2005), pulmonary function or injury (Clark et al 1990;Dubick et al 2002;Hubbard et al 1991;Ischiropoulos et al 1994;Jeng et al 2003;Lin et al 2001;Park et al 2004;Steinberg et al 2005;Thorning et al 1982), effects on surfactant (Jeng et al 2003;, inflammation (Bhattacharyya et al 2004;Huang et al 2006), epithelial damage (Bhattacharyya et al 1998), edema Nieman et al 1995), apnea , and antibacterial activity (Fick et al 1984;Pimenta et al 2000). Extrapulmonary assessments have included effects on the cardiovascular system (Brizio-Molteni et al 1984), adjuvant activity (Samuelsen et al 2008 (Bhattacharyya et al 1998;Liang et al 1988;Mumford et al 1990).…”
Section: Parameters Assayedmentioning
confidence: 99%